Synthesis and investigation of anti-inflammatory and anticonvulsant activities of novel coumarin-diacylated hydrazide derivatives - ÇAM, MUHAMMET EMİN (ELSEVIER, 2020)
A number of novel coumarin derivatives synthesized by the reaction of 3-carbonyl chloride coumarin with some substituted aryl acid hydrazides to investigate their anti-inflammatory and anticonvulsant activities. Carrageenan (0.1 ml of 1%, w/v) was injected subplantarly in the right paw of rats to induce an acute model of inflammation. Anti-inflammatory efficacy was evaluated for 5 hours at 3 different dosages 5, 10, 25 mg/kg. After that, the changes in the level of paw edema volumes and percentage inhibition of all groups were observed and the most effective coumarin derivative was found as N'-(2-hyroxybenzoyl)-2-oxo-2H-chromene-3-carbohydrazide. In addition, N'-(2-oxo-2H-chromene-3-carbonyl)nicotinohydrazide, (E)-N'-(3-(4-hydroxyphenyl)acryloyl)-2-oxo-2H-chromene-3-carbohydrazide, and N'-(5-amino-2-hydroxybenzoyl)-2-oxo-2H-chromone-3carbohydrazide showed their anti-inflammatory effects in a dose-dependent manner. On the other hand, pentylenetetrazole (PTZ, 80 mg/kg, i.p.)-induced seizure model was used to investigate the anticonvulsant activities of six newly synthesized coumarin derivatives in mice. Hybrid compound of salicylic acid hydrazide and 3-carbonyl chloride coumarin (8d) was found the most promising anticonvulsant agent among all treatment groups according to the onset of seizure and survival rate. Moreover, (E)-N'-cinnamoyl-2-oxo-2H-chromene-3-carbohyrazide (8b) and (E)-N'-(3-(4-hyroxy phenyl)acryloyl)-2-oxo-2H-chromene-3-carbohydrazide (8c) has potential anticonvulsant efficiency in low doses (30 mg/kg). The anticonvulsant effect of these coumarin derivatives may be through enhanced GABA-mediated inhibition in the brain. (C) 2020 Published by Elsevier B.V. on behalf of King Saud University.
Keywords: Anti-inflammatory activity; Anticonvulsant activity; Coumarin-diacylated hydrazide; Pentylenetetrazole-induced seizures; Carrageenan-induced paw edema; N,N'-DIACYLHYDRAZINE DERIVATIVES; BIOLOGICAL-ACTIVITIES; ACID-DERIVATIVES; SEIZURE ACTIVITY; ANTIOXIDANT; EPILEPSY; EXTRACT; METHYL; BIOACTIVITY